Saudi Arabia’s Interets in Singing The Dedollarization Agreement with China in 2023 - Amelia, Lisa; Wicaksa, Arif (Mutiara: Multidiciplinary Scientifict Journal, 2025)
This research explains that Saudi Arabia's interest in signing the dedollarization agreement with China was driven by several factors. First, international factors, such as the strained relationship with the United States following the murder of Jamal Khashoggi and the reduction of U.S. military support, which prompted Riyadh to seek alternative partnerships. Second, the absolute monarchy under Crown Prince Mohammed bin Salman allows for the unilateral implementation of economic diversification and dedollarization visions, aimed at strengthening domestic legitimacy and creating a more stable economy. Third, economic and military factors, which heavily depend on oil exports and are affected by price fluctuations and the rise of shale oil in the U.S., also encouraged Saudi Arabia to take this strategic step as an effort to strengthen national stability and seek alternative trade partnerships in the oil sector.